The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/v15081655
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial-Derived Immune Mediators in COVID-19

Tony J. F. Guo,
Gurpreet K. Singhera,
Janice M. Leung
et al.

Abstract: The airway epithelium, which lines the conducting airways, is central to the defense of the lungs against inhaled particulate matter and pathogens such as SARS-CoV-2, the virus that causes COVID-19. Recognition of pathogens results in the activation of an innate and intermediate immune response which involves the release of cytokines and chemokines by the airway epithelium. This response can inhibit further viral invasion and influence adaptive immunity. However, severe COVID-19 is characterized by a hyper-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…This study enrolled 79 severely diseased patients with COVID-19 and 72 healthy individuals as a control group. Many articles about the increased level of IL-6 and its role as an important indicator of severe COVID-19 (14)(15)(16)(17)(18) led us to think about the correlation of this marker with DHEA-S, as several reports revealed the inverse correlation between these two parameters (19)(20)(21). Among current study patients, the gender distribution showed nearly equal involvement of both sexes, with a slight preference towards males, which goes with Zaher K. et al, 2023 (22) and Jian-Min J. et al, 2020 (23) who describe the gender distribution among severely affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study enrolled 79 severely diseased patients with COVID-19 and 72 healthy individuals as a control group. Many articles about the increased level of IL-6 and its role as an important indicator of severe COVID-19 (14)(15)(16)(17)(18) led us to think about the correlation of this marker with DHEA-S, as several reports revealed the inverse correlation between these two parameters (19)(20)(21). Among current study patients, the gender distribution showed nearly equal involvement of both sexes, with a slight preference towards males, which goes with Zaher K. et al, 2023 (22) and Jian-Min J. et al, 2020 (23) who describe the gender distribution among severely affected patients.…”
Section: Discussionmentioning
confidence: 99%